Legal Protection and Rights of Indigenous Peoples: Legal Certainty in Managing Natural Resources - Yuniar Rahmatiar (Faculty of Law, Universitas Pekalongan, 2023)
Indigenous peoples possess traditional rights to natural resources within their territories, yet these rights are frequently overlooked or marginalized due to inadequate policies and regulations. This research aims to examine the legal protection of the Baduy tribe's rights in managing natural resources and to explore how legal certainty can be achieved in this regard. Utilizing a normative juridical approach, the study analyzes relevant laws and regulations pertaining to indigenous rights and state-provided legal protection. The findings reveal that the recognition and protection of customary law communities in Indonesia highlight the state's commitment to supporting social entities with autonomy over their lives. Despite the pressures of modern integration, indigenous peoples continue to uphold their identity, traditions, and customary rights. Legal acknowledgment of these rights is enshrined in the 1945 Constitution and various laws, including Law No. 5 of 1960 on Agrarian Affairs, Law No. 4 of 2009 on Mining, Law No. 41 of 1999 on Forestry, and Law No. 7 of 2004 on Water Resources. However, effective implementation is often hindered by regulations that do not adequately address customary rights. While Constitutional Court Decision No. 35 of 2012, which recognizes customary forests as belonging to indigenous communities, represents significant progress, challenges persist. The need for revisions to create more inclusive laws or regulations is pressing. For the Baduy tribe, Lebak Regency Regional Regulation (Perda) Number 32 of 2001 on the Protection of Ulayat Rights is a critical development. This regulation offers legal certainty and safeguards their traditional rights, including customary land and natural resources, and tackles issues like illegal logging and forest encroachment. By acknowledging local wisdom and customs, this regulation aims to preserve Baduy culture and enhance security and social stability in their area.